Active and passive Q-switching operation of 1 μm Yb:YSP laser with an optical chopper/AOM and MoWS2 nanosheets. (1st December 2022) - Yin, Xiaoqin; Fan, Shuzhen; Zhang, Xingyu; Wu, Guangda; Yu, Fapeng
Abstract: In this paper, the laser diode (LD)-pumped all-solid-state Yb:YSr3 (PO4 )3 (Yb:YSP) lasers with active and passive Q-switching operation were demonstrated for the first time. At the pump power of 5.5 W, the average output power was 369 mW and the single pulse energy was 184.5 μ J at 2 kHz in the active Q-switching operation with an optical chopper. For the acousto-optic modulator Q-switched laser, a 118 ns pulse duration and 2881 W pulse peak power at 0.5 kHz were obtained. Furthermore, MoWS2 nanosheets were implemented to the passively Q-switched Yb:YSP laser, generating stable pulses with duration of 1.45 μ s at the repetition frequency of 55 kHz and verifying the optical response potential of MoWS2 . The good laser beam quality of M x 2 = 1.14 and M y 2 = 1.12 were achieved as well.